The relation between particle number concentration and high frequency sound level of traffic noise - Kim, Sung Min (2019)
Relation between particle number concentration (PNC) and traffic conditions were investigated through field measurements and statistical analysis. Traffic data for 24 hours in an urban area where close to three traffic roads, and the particle number concentration were measured within 0.3 to 10 μm. The results show that traffic speed and noise level of traffic have negative correlation in low frequency band, and relationship between traffic volume and traffic noise has negative correlation in mid frequency. In addition, the correlation between particles and traffic noise indicates that high frequency sound increase the concentration of particles road side area. Especially correlation between LAeq and PNC size range from 0.3 - 1.0 μm shows positive relationship with percentile noise indicators. The findings of this study suggest that information of the particle distribution with the noise can be used as important indicators to predict air and noise pollution of urban areas.